Dependence of bending strength on orientations of KDP crystals. Issue 9 (10th February 2022) - Huang, Pingping; Liu, Hui; Zhang, Liyuan; Li, Xianglin; Wang, Shenglai
Abstract : The bending strength of KDP crystals with different orientations was measured to study the anisotropy and size dependence of fracture strength. Abstract : The bending strength anisotropy on the (001) plane or between the (100) and (001) planes of KDP crystals was investigated via a three-point bending test. Fracture surfaces were observed. Moreover, the defect distribution of the KDP samples was also analyzed. The results indicated that the bending strength along the [001] direction was higher than that along multiple directions on the (001) plane, showing pronounced anisotropy. However, the bending strengths along different directions on the (001) plane were similar. For the fractured samples with different orientations, multiple fracture surfaces for the (001), (100), (110), (2̄10), (310) planes were observed. It was also deduced from the linear elastic fracture mechanism that the surface or internal defects with a dimension of 0.1 mm existed in the samples.